Shear tests of hollow flange channel beams with real support conditions. (August 2015) - Keerthan, Poologanathan; Mahendran, Mahen; Narsey, Anand
Abstract: This paper presents the details of experimental studies on the effect of real support conditions on the shear strength of hollow flange channel beams, known as LiteSteel beams (LSBs). The LSB has a unique shape of a channel beam with two rectangular hollow flanges, made using a unique manufacturing process. In many applications in the building industry LSBs are used with only one web side plate (WSP) at their supports. The WSPs are also often not full height plates. Past research studies showed that these real support connections did not provide the required simply supported conditions. Many studies have been carried out to evaluate the behaviour and design of LSBs with simply supported conditions subject to pure bending and predominant shear actions. To date, however, no investigation has been conducted into the effect of real support conditions on the shear strength of LSBs. Hence a detailed experimental study based on 25 shear tests was undertaken to investigate the shear behaviour and strength of LSBs with real support conditions. Simply supported test specimens of LSBs with aspect ratios of 1.0 and 1.5 were loaded at mid-span until failure. It was found that the effect of using one WSP on the shear behaviour of LSB is significant and there is about 25% shear capacity reduction due to the lateral movement of the bottom flange at the supports. Shear capacity of LSB was also found to decrease when full height WSPs were not used. Suitably improved support connections were developed to improve the shear capacity of LSBs based on test results. Details of the recommended support connections and shear capacity results are given in this paper.